Pop-Up Book Sebagai Media untuk Meningkatkan Pengetahuan Siswa Sekolah Dasar tentang Konsumsi Makanan Kariogenik - Ananta, Indriyani; Larasati, Ratih; Isnanto, Isnanto (FORIKES, 2025)
Cariogenic foods are foods that contain high levels of sugar, which can cause cavities. The high incidence of caries in children can be caused by the limited knowledge of children about the consumption of cariogenic foods. The knowledge that will be conveyed to children must attract attention so that the information conveyed can be accepted. The purpose of this study was to determine the effectiveness of using pop-up book media on increasing knowledge about the consumption of cariogenic foods in elementary school students. This study used a one group pretest-posttest design involving 33 sixth grade students of SDN Marengan Laok 1, Sumenep. The level of knowledge in the phases before and after counseling with pop-up book media was measured by filling out a questionnaire. Furthermore, a comparative analysis of the level of knowledge between before and after the intervention was carried out using the Wilcoxon test. The results of the analysis showed that before the intervention, the highest level of knowledge was sufficient (68%); while after the intervention, the highest level of knowledge was good (95%). The p-value from the results of the comparative analysis of the level of knowledge was 0.000, so it was interpreted that there was a significant difference in the level of knowledge between before and after counseling using pop-up book media. Furthermore, it could be concluded that counseling with pop-up book media is effective in increasing elementary school students' knowledge about the consumption of cariogenic foods.Keywords: cariogenic foods; students; elementary school; knowledge; pop-up book media ABSTRAK Makanan kariogenik merupakan makanan yang mengandung tinggi akan gula, yang dapat menyebabkan gigi berlubang. Tingginya angka kejadian karies pada anak salah dapat disebabkan oleh keterbatasan pengetahuan anak tentang konsumsi makanan kariogenik. Pengetahuan yang akan disampaikan kepada anak harus menarik perhatian sehingga informasi yang disampaikan dapat diterima. Tujuan penelitian ini adalah mengetahui efektivitas penggunaan media pop-up book terhadap peningkatan pengetahuan tentang konsumsi makanan kariogenik pada siswa sekolah dasar. Penelitian ini menggunakan rancangan one group pretest-posttest dengan melibatkan 33 siswa kelas VI SDN Marengan Laok 1, Sumenep. Tingkat pengetahuan pada fase sebelum dan sesudah penyuluhan dengan media pop-up book diukur melalui pengisian kuesioner. Selanjutnya dilakukan analisis perbandingan tingkat pengetahuan antara sebelum dan sesudah intervensi menggunakan uji Wilcoxon. Hasil analisis menunjukkan bahwa sebelum intervensi, tingkat pengetahuan terbanyak adalah cukup (68%); sedangkan sesudah intervensi, tingkat pengetahuan terbanyak adalah baik (95%). Nilai p dari hasil analisis perbandingan tingkat pengetahuan adalah 0,000, sehingga diinterpretasikan bahwa ada perbedaan tingkat pengetahuan secara signifikan antara sebelum dan sesudah penyuluhan menggunakan media pop-up book. Selanjutnya dapat disimpulkan bahwa penyuluhan dengan media pop-up book efektif untuk meningkatkan pengetahuan siswa sekolah dasar tentang konsumsi makanan kariogenik.Kata kunci: makanan kariogenik; siswa; sekolah dasar; pengetahuan; media pop-up book